Community-based participatory research on the impact of greenspace on violent crime - Mardelle McCuskey Shepley; Rebecca Lauren Ames; Renata Marques Leitão; Gloria Coleman (IOP Publishing, 2022)
Background. The positive impact of greenspace on human health has been well documented, including several literature reviews and meta-analyses that have examined the broad benefits of nature connections. Researchers have also examined the relationship between nature and crime reduction and identified potential mechanisms underlying this outcome, such as the physiological impact of nature, lowered temperatures due to a reduction in the heat island effect, and places for community interaction. However, a critical shortcoming of this study is the lack of deep community involvement in the research process. Community-based participatory research (CBPR) is critical to ensuring that the findings are meaningful to communities and translatable. This study expands on recent literature reviews on greenspace outcomes by focusing on community-engaged research (CER). By gathering and summarizing studies on this topic, we address two subjects: (a) strategies that can be used to improve community engagement, and (b) environmental factors that impact community outcomes in greenspace settings. Methods. To explore these issues, we used a modified version of Arksey and O'Malley's framework for a structured literature review, employing the Web of Science, EbscoHost, Scopus, ProQuest Global, and Google Scholar databases. Results. We retrieved 772 publications using permutations of keywords related to violent crime, greenspaces, and CBPR. After eliminating duplicates, the reviewers worked in parallel to evaluate 700 titles and abstracts and identified 51 potentially relevant papers, ten of which met the requirements for inclusion in this analysis. Discussion. Based on the studies explored in this literature review, we identified the following strategies for improving CER: building partnerships, facilitating power-sharing, utilizing community-specific indicators of success, embracing perspectives of communities of color, and empowering community researchers. In the sample of studies described here, the factors contributing to the relationship between greenspace and violent crime were maintenance, activity programming, green interventions, and community involvement.